Trans-umbilical Single-Site Plus One Robotic Assisted Surgery for Choledochal Cyst in Children, a Comparing to Laparoscope-Assisted Procedure - Lin, Shan; Chen, Jianglong; Tang, Kunbin; He, Yufeng; Xu, Xinru; Xu, Di (Frontiers in Pediatrics, 2022)
Objective：Introduce the trans-umbilical single-site plus one robotic assisted surgery in treatment of pediatric choledochal cyst. Compare the intraoperative and postoperative outcomes between the trans-umbilical single-site plus one robotic assisted surgery and traditional laparoscope-assisted procedure. Method: We retrospectively analyzed the clinical data of 51 children diagnosed with choledochal cysts and received surgery from June 2019 to December 2020 at our department. 24 patients underwent Robot-assisted procedure were selected as R group and 27patients underwent laparoscope-assisted were selected as L group. We compare the intraoperative and postoperative outcomes between two groups. Result: No significant differences were found in demographic information between two group(P>0.05).The median total operative time, median port/trocar installation time, median wound suture time of R group were longer than L group (217.63±5.90 min vs. 199.37±5.13min; 30.71±3.18min vs. 6.11±1.15min; 30.79±1.82min vs. 10.85±1.97min; respectively, p < 0.001). But R group had shorter mean extracorporeal Roux-y jejunojejunostomy time, choledochal cyst excision time and mean hepaticojejunostomy anastomosis time than L group(52.67±3.53min vs. 62.52±3.40min; 52.04±2.74min vs. 59.26±3.23min; 52.42±2.72min vs. 60.63±3.30min; respectively, p < 0.001). R Group also had less mean volume of blood loss (7.04±1.16ml vs. 29.04±18.21ml; p < 0.001). R Group had shorter anal exhaust time, water feeding time, solids feeding time, hospital stay time, indwelling time of gastric tube than L group (p < 0.05) after surgery. R Group had a lower early complication rate than L group (4.2% vs. 29.63%; p = 0.026). No statistical differences were identified between two groups in late or any single complication (0.00% vs. 11.11%; p＞0.05). Conclusion: Trans-umbilical single site plus one robot-assisted surgery can achieve better intraoperative and postoperative outcomes compared with laparoscopic surgery in pediatric choledochal cyst. The umbilical incision is more concealed and beautiful. Combing the experience of single-site surgery with robot-assisted surgery, the operators can implement the technique in children safely and feasibly